Cytotoxic effects of curcumin in osteosarcoma cells - Moran JM (Dove Medical Press, 2014)
JM Moran, FJ Rodriguez-Velasco, R Roncero-Martin, V Vera, JD Pedrera-Zamorano Metabolic Bone Diseases Research Group, University of Extremadura, Cáceres, SpainWe read with interest the results of the study from Chang et al1 in the International Journal of Nanomedicine. This article shows that curcumin (diferuloymethane), a phenolic compound extracted from the natural plant Curcuma longa L., exerts higher cytotoxicity in osteosarcoma MG-63 cells than in healthy human osteoblasts. Based on the dosages provided by the authors it is hypothesized that with the appropriate drug carriers, curcumin could be delivered to bone tumors and selectively kill osteosarcoma cells without harming healthy osteoblasts. This hypothesis is based in the data provided that claims the dose needed to exert a significant cytotoxicity on osteosarcoma cells was much lower than that needed to exert the same effect on healthy human osteoblasts. The topic of this study is of importance for both cancer and metabolic bone disease fields, we appreciate the methodology of the study, nevertheless we believe that the hypothesis formulated by the authors and their conclusion deserves further comment.View original paper by Chang and colleagues.